Peran Guru Dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Kemuhammadiyahan - Matondang, Salsabila; Afandi, Ahmad (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
The teacher is a figure who plays an important role in the learning process to improve student development as appropriate. Teachers are mentors and motivators in the learning and education process of students. It can be concluded that the teacher's role in encouraging student learning is as a motivator, information provider, organizer, influencer/director, initiator, facilitator, mediator, and evaluator (evaluator). To arouse students' interest in learning, it is necessary to have a professional teacher's role in educating students to become well-educated people. Student interest in learning is a strong encouragement arising from student motivation and experience so that they know how to do it to perfect the knowledge they want to achieve. By carrying out this research, it is aimed that teachers play a very important role in increasing students interest in learning. This research is field research conducted at MTs.Muhammadiyah-13. This research aims to describe the role of using learning media in increasing students' interest in learning. This research uses a qualitative analysis method where the data obtained comes from interview techniques, observation, and documentation. Therefore, the results are based on existing data and information.